1999
DOI: 10.1179/026708399101506805
|View full text |Cite
|
Sign up to set email alerts
|

Friction welding process of 5052 aluminium alloy to 304 stainless steel

Abstract: T ype 5052 aluminium alloy was joined to type 304 austenitic stainless steel via a continuous drive friction welding process. T he joint strength increased, and then decreased after reaching a maximum value, with increasing friction time. Joint strength depended on the size and shape of the tensile testpiece. Friction weldability could be estimated by electrical resistmetry. T he process of friction welding between the aluminium alloy and the stainless steel is proposed to evolve as follows: welding progresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
58
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(62 citation statements)
references
References 6 publications
3
58
0
1
Order By: Relevance
“…Steel and aluminium are commonly joined by mechanical means like screwing, riveting or clinching, but also with solid state welding processes like explosion welding, 1 friction welding, 2 or more recently by friction stir welding. 3 In contrast, steel to aluminium fusion welding remains a technological issue due to the great difference in physical properties of both materials (melting temperature, coefficient of thermal expansion…) and most of all because of the near zero solid solubility of iron in aluminium, which involves the creation of brittle intermetallic phases.…”
Section: Introductionmentioning
confidence: 99%
“…Steel and aluminium are commonly joined by mechanical means like screwing, riveting or clinching, but also with solid state welding processes like explosion welding, 1 friction welding, 2 or more recently by friction stir welding. 3 In contrast, steel to aluminium fusion welding remains a technological issue due to the great difference in physical properties of both materials (melting temperature, coefficient of thermal expansion…) and most of all because of the near zero solid solubility of iron in aluminium, which involves the creation of brittle intermetallic phases.…”
Section: Introductionmentioning
confidence: 99%
“…Friction welding of various materials was the subject of these authors previous research [1][2][3], as well as of certain other authors [4][5][6][7][8][9][10][11]. In those articles, it was shown that successful joining by friction welding could be done for different classes of steel [1][2][3][4][5], steels and other metals [6] or the light metals [7][8][9][10]. In addition, joints realized by classical friction welding, considered in this paper, can be compared to joints obtained by the friction stir welding procedure [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Ylbas et al [4] investigated the mechanical and metallurgical properties of friction welded steel-aluminium and aluminiumcopper. Fukumoto S et al [1,5] studied the friction welding set up and the strength of the joints and investigated amorphization process between aluminium alloy and stainless steel by friction welding. Furthermore the cleanliness of the parts must be considered as important.…”
Section: Introductionmentioning
confidence: 99%